2021
DOI: 10.3390/cancers13235909
|View full text |Cite
|
Sign up to set email alerts
|

A Novel Prognostic Biomarker Panel for Early-Stage Colon Carcinoma

Abstract: Molecular characterization of colorectal cancer has helped us understand better the biology of the disease. However, previous efforts have yet to provide significant clinical value in order to be integrated into clinical practice for patients with early-stage colon cancer (CC). The purpose of this study was to assess PD-L1, GLUT-1, e-cadherin, MUC2, CDX2, and microsatellite instability (dMMR) and to propose a risk-panel with prognostic capabilities. Biomarkers were immunohistochemically assessed through tissue… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 87 publications
0
3
0
Order By: Relevance
“…Three-μm sections of tissue microarrays (TMAs) blocks harboring four tumor-carrying cores selected by the pathologist were placed on slides and then deparaffinized, hydrated and treated to block endogenous peroxidase activity using Vision Biosystems Bond-Max (Leica, Wetzlar, Germany) and Bench-Mark XT Ventana (Roche, Basel, Switzerland) automatic immunostaining apparatus, as previously published [ 64 ]. These slides were incubated with the appropriate primary antibodies against mismatch repair proteins-MMR (MLH1, MSH2, MSH6) and against proteins of the subrogate panel (CDX2, FRMD6, HTR2B and ZEB1) under the conditions summarized in Additional file 5 : Table 1.…”
Section: Methodsmentioning
confidence: 99%
“…Three-μm sections of tissue microarrays (TMAs) blocks harboring four tumor-carrying cores selected by the pathologist were placed on slides and then deparaffinized, hydrated and treated to block endogenous peroxidase activity using Vision Biosystems Bond-Max (Leica, Wetzlar, Germany) and Bench-Mark XT Ventana (Roche, Basel, Switzerland) automatic immunostaining apparatus, as previously published [ 64 ]. These slides were incubated with the appropriate primary antibodies against mismatch repair proteins-MMR (MLH1, MSH2, MSH6) and against proteins of the subrogate panel (CDX2, FRMD6, HTR2B and ZEB1) under the conditions summarized in Additional file 5 : Table 1.…”
Section: Methodsmentioning
confidence: 99%
“…Numerous studies analyzed the gene transcriptional levels of colon cancer patients and found key genes such as GLUT1, MUC2, Cyclooxygenase-2, etc. that are related to the prognosis of colon cancer [3,4]. Recent studies on colon cancer-related gene regulatory pathways found that MAPK signaling pathway, JAK/STAT, AKT/NF-κB and other signaling pathways can modulate the occurrence of colon cancer [5][6][7].…”
Section: Introductionmentioning
confidence: 99%
“…Numerous groups have since reproduced the prognostic claims [11][12][13][14][15][16][17][18][19][20][21][22][23][24] . Thirty-two independent studies, involving >13,000 unique subjects, most that used IHC and one that used IHC in combination with quantitative mass spectrometry 25 , have determined that CDX2-neg CRCs are associated with lower overall survival (OS) and DFS independent of ethnicity, DNA mismatch repair (MMR) status or stage 7,20,24,26 [Figure 1- Step 1].…”
Section: Introductionmentioning
confidence: 99%